Review—Electronic Circuit Systems for Piezoelectric Resonance Sensors. Issue 3 (3rd February 2020) - Park, Jong-Yoon; Choi, Jin-Woo
Abstract : Piezoelectric mass sensors have been widely studied for a variety of applications as a biological or chemical sensing transducer. With an increasing range of application areas and performance requirements for fast measurement time, higher resolution and accuracy, and compact system size, different measurement electronic systems have also been investigated to fulfill the performance requirements. Selecting a proper type of measurement electronics is critical to develop an optimized sensing system for practical applications. In this review, we cover different types of measurement electronics configurations including impedance-based measurement, oscillator-based measurement, and ring-down technique. Also, we provide an overview of the recent advances of each measurement electronics configuration for piezoelectric resonator sensors. Finally, the pros and cons of each measurement electronic configuration are compared and discussed.